INTERVENSI POSITIONAL RELEASE TECHNIQUE DAN INFRARED SAMA BAIK DENGAN INTERVENSI CONTRACT RELAX STRETCHING DAN INFRARED DALAM MENURUNKAN NYERI KEPALA AKIBAT KETEGANGAN OTOT UPPER TRAPEZIUS PADA PEGAWAI KANTORAN - Made Kristira Yanti; Ni Luh Nopi Andayani; I Putu Adiartha Griadhi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACTHeadache can be caused by increased tension in upper trapezius muscle. This headache is characterized bytrigger point and upper trapezius muscle tautband. The purpose of this study was to compare the positional releasetechnique and infrared interventions with contract relax stretching and infrared on the reduction of headache due toupper trapezius muscle tension. This study was experimental with pre and post-test group design designs of 24 peopledivided into two groups. Group 1 received positional release technique and infrared, while Group 2 received contractrelax stretching and infrared. The result of data analysis with paired sample t-test in Group 1 showed the average 2,242± 0,329 and p = 0,001, while Group 2 showed the average 2,225 ± 0,201 and p = 0,001. From the results of the analysisshowed in each group there is a significant reduction of pain. Based on independent samples test t-test between groups1 and 2 obtained p value = 0.882 (p> 0.05). It can be concluded that the positional release technique and infraredintervention has no significant difference as contract relax stretching and infrared to decreased headache due to uppertrapezius muscle tension.Keywords: Headache, upper trapezius muscle, positional release technique, contract relax stretching, infrared, VAS